Computer Hardware Resources E-commerce Platform Based on Intelligent Recommendation and High Concurrency Processing - "Beiji Technology" - Luo, Youyi; Jiang, Ting (IC-ITECHS, 2024)
With the rapid development of e-commerce and the diversification of the computer hardware market, consumers are facing more and more difficulties in choosing computer accessories, and traditional e-commerce platforms are difficult to meet the user's demand for accurate shopping and efficient recommendation. The purpose of this paper is to build an intelligent computer accessories shopping platform (Beiji Technology), through intelligent recommendation algorithms, to improve the user shopping experience. The platform adopts mainstream front-end technology, efficient and stable back-end architecture, supports high concurrency data processing, and at the same time realizes dynamic interaction, which enhances the responsiveness and smoothness of the user interface. Its intelligent recommendation system generates personalized accessory recommendations based on the user's historical behavior, helping users find the products they need faster. The realization of this platform not only solves the pain points of traditional e-commerce platforms in the purchase of computer accessories, but also promotes the development of the e-commerce industry in the direction of intelligence and precision, and provides valuable references for the future research and practice of intelligent e-commerce.